Effect of Pumping Depth on Hydraulic Conductivity Measurement by Auger Hole Method - Jhorar, Raj Kumar; Anjaneyulu, B (Journal of Agricultural Engineering, 2009)
The flow dynamics of auger hole method, used for hydraulic conductivity measurements, was examined with the help of streamlines. Values of stream function around an auger hole penetrating to an impervious layer were calculated for different depths of pumped water level in the hole. Streamlines were drawn around an auger hole for four cases of pumped water level- auger hole empty, one-fourth full, half full and three-fourth full. Examination of streamlines highlighted the consequence of change in pumped water level on flow toward the auger hole. Contrary to the earlier belief that auger hole measurements give average horizontal saturated hydraulic conductivity of the soil zone from static water table level to the bottom of the auger hole, it is shown that this is true only in case of uniform isotropic soils. It is suggested that the auger hole tests for subsurface drainage design must be conducted with very small amount of pumping (say 25 %) so that the soil region and flow direction used for measurement of saturated hydraulic conductivity adequately represent the soil and flow direction in the actual system. It was also observed that the measured value of saturated hydraulic conductivity, particularly for a soil with variable conductivity with depth, would be more representative of the average if measurements are taken with small depth of water pumped from the hole.